Strengthening National Defense: Quality Management in Indonesian Army (TNI AD) Curriculum Development - Joni Widjayanto; Priyanto Priyanto (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research aims to analyze and describe the curriculum development management policies in the Indonesian Army's Infantry Education Center and Cavalry Education Center to enhance the quality of education curricula. This research employs a qualitative approach, using management and quality theories as analytical instruments. The management functions, including planning, organizing, implementing, and monitoring, are phased out according to these theories. Data collection procedures involve interviews, document analysis, and observations. The research findings reveal key aspects of the planning phase that need optimization. The combination of critical thinking and experience can lead to wisdom. Comparative studies can be beneficial when positive elements can be applied within educational institutions. Based on the research results, it is recommended that an organization that functions as a quality assurance body within the Infantry Education Center and Cavalry Education Center be established. Continuous human resource quality enhancement is also suggested to improve curriculum quality development management. It is hoped that various challenges in education implementation can be overcome, ultimately achieving the effective and efficient development of curricula.